THE INFLUENCE OF STUDENT’S SELF CONCEPT ON SELF- ACCEPTANCE AT THE ORPHANAGE - Findy Suri; Sri Yuliani (Sean Institute, 2023)
This study aims to determine the correlation between self-concept and self-acceptance in adolescents at the Puteri Aisyiyah orphanage. The problem is focused on adolescents in orphanages who lack good self-acceptance which also affects the formation of the adolescent's self-concept. To approach this problem, the theoretical reference from Sheerer (in Utami, 2013) is used for self-acceptance and the theory from Fitts (in Agustiani & Hendrianti, 2006) for the self-concept. The data were collected through a collection process using a Likert scale with the calculation of product moment analysis and analyzed quantitatively. The results of this study indicate that there is a positive and significant correlation between self-concept and self-acceptance of orphanage adolescents where (rxy) is 0.892 with a significance of p = 0.000 < 0.050. The coefficient of determination of this correlation is r₂ = 0.795, meaning that self-concept contributes to self-acceptance of 79.5%. The self-concept in this study is classified as positive because (hypothetical mean = 110 < empirical mean = 149.52), while self-acceptance in this study is relatively high (hypothetical mean = 92.5 < empirical mean 122.48).